ChemInform Abstract: Ionothermal Synthesis and Magnetic Study of a New Manganese(II) Phosphite with an unprecedented Mn/P Ratio. Issue 38 (September 2016) - Su, Tan; Xing, Hongzhu; Li, Yi; Wu, Junbiao; Song, Xiaowei; Nakano, Takehito; Yu, Jihong
Abstract: The layered Mn(II) phosphite (NH4 )4 [Mn4 (PO3 H)6 ] is prepared by ionothermal reaction of MnCl2 ·4H2 O, H3 PO3, and NH4 F using 1‐pentyl‐3‐methylimidazolium bromide ([pmim]Br) as the solvent (autoclave, 150 °C, 7 d, ≈70% yield).